Characteristics of Child-friendly Cities: A Bibliometric Study - Kasmita, Maya; Niswaty, Risma; Heri, Ririn Nurfaathirany (Sawwa: Jurnal Studi Gender, 2024)
Women and children are two groups that are particularly susceptible to exploitation and violence. As women and children must be protected from all forms of violence and exploitation and conditioned with education and care so that all of their potential and talents can grow and develop optimally, women must be empowered to be independent and self-reliant without forgetting their nature. In order to enhance performance, this study examines urban planning and metrics of kid-friendly cities. Google Scholar is used to find credible and nationally accredited journals for this literature review, which uses articles from a variety of studies. According to the study, child-friendly cities only became popular in 2018, and very few Indonesian cities—especially Makassar—have adopted these ideas. More studies on social impact, children's autonomous mobility, playgrounds, city planning, safety, community, smart cities, kid-friendly environments, social evolution, health initiatives, transportation, and poverty are needed, according to the study. The study intends to serve as a guide for enhancing performance in cities that are kid-friendly.